Updating search strategies for literature reviews with OUR2D2: an open-source computer application. - Lohr, Abby M.; Van Gorden, Noah; McClelland, D. Jean; Dubinsky, Ellen; Gerald, Lynn B.; Wilkinson-Lee, Ada; Carvajal, Scott C. (Journal of the Medical Library Association, 2021)
Background: While writing a scoping review, we needed to update our search strategy. We wanted to capture articles generated by our additional search terms and articles published since our original search. Simultaneously, we strove to optimize project resources by not rescreening articles that had been captured in our original results. Case presentation: In response, we created Open Update Re-run Deduplicate (OUR2D2), a computer application that allows the user to compare search results from a variety of library databases. OUR2D2 supports extensible markup language (XML) files from EndNote and comma-separated values (CSV) files using article titles for comparisons. We conducted unit tests to ensure appropriate functionality as well as accurate data extraction and analysis. We tested OUR2D2 by comparing original and updated search results from PubMed, Embase, Clarivate Web of Science, CINAHL, Scopus, ProQuest Dissertation and Theses, and Lens and estimate that this application saved twenty-one hours of work during the screening process. Conclusions: OUR2D2 could be useful for individuals seeking to update literature review strategies across fields without rescreening articles from previous searches. Because the OUR2D2 source code is freely available with a permissive license, we recommend this application for researchers conducting literature reviews who need to update their search results over time, want a powerful and flexible analysis framework, and may not have access to paid subscription tools.